A multiplex TaqMan real-time PCR assays for the rapid detection of mobile colistin resistance (mcr-1 to mcr-10) genes - Gong, Xinran; Yang, Guang; Liu, Wei; Wu, Di; Duan, Chunyuan; Jia, Xinjing; Li, Zhiqiang; Zou, Xiaocang; Yu, Renfeng; Zou, Dayang; Wang, Yong (Frontiers in Microbiology, 2024)
Objective: Recently, 10 plasmid-mediated mobile colistin resistance genes, mcr-1 to mcr-10, and their variants have been identified, posing a new threat to the treatment of clinical infections caused by Gram-negative bacteria. Our objective was to develop a rapid, sensitive, and accurate molecular assay for detecting mcr genes in clinical isolates.Methods: The primers and corresponding TaqMan-MGB probes were designed based on the sequence characteristics of all reported MCR family genes, multiplex Taqman-MGB probe-based qPCR assays were developed and optimized, and the sensitivity, specificity and reproducibility of the method were evaluated. The assay contained 8 sets of primers and probes in 4 reaction tubes, each containing 2 sets of primers and probes.Results: The standard curves for both the single and multiplex systems showed good linearity (R 2 > 0.99) between the starting template amount and the Ct value, with a lower limit of detection of 10 2 copies/μL. The specificity test showed positive amplification results only for strains containing the mcr genes, whereas the other strains were negative. The results of intra-and inter-group repeatability experiments demonstrated the stability and reliability of the newly developed method. It was used to detect mcr genes in 467 clinically-obtained Gram-negative isolates, which were multidrug-resistant.Twelve strains containing the mcr genes were detected (seven isolates carrying mcr-1, four isolates carrying mcr-10, and one isolate carrying mcr-9). The products amplified by the full-length PCR primer were identified by sequencing, and the results were consistent with those of the multiplex qPCR method.The assay developed in this study has the advantages of high specificity, sensitivity, and reproducibility. It can be used to specifically detect drug-resistant clinical isolates carrying the mcr genes (mcr-1 to mcr-10), thus providing a better basis for clinical drug treatment and drug resistance research.